Progressive Feature Enhancement for Person Re-Identification - Zhong, Yingji (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2021)
Most of person Re-Identification (ReID) works extract features from the top CNN layer for person image matching. The top CNN layer commonly corresponds to large receptive fields, thus is not effective in depicting visual cues at multiple scales, e.g., both global appearance and local details. This work proposes a Progressive Feature Enhancement (PFE) algorithm to spot and fuse multi-scale discriminative cues from different CNN layers into a single feature vector. The basic idea is to progressively learn complementary features with a layer-specific supervision from deep to shallow layers. The layer-specific supervision is inferred by the proposed Masked Feature Augmentation (MFA) module. For each CNN layer, MFA indicates cues that have been captured in its deeper layers. MFA hence supervises each layer to depict additional visual cues missed by its deeper layers. This framework effectively learns multi-scale features without requiring extra part annotations or dividing body parts. To further facilitate the layer-specific feature generation, a Two-Stage Attention Module (TSAM) is proposed to filter pixel-wise and channel-wise noises on intermediate feature maps. Extensive experiments on four ReID datasets show that our approach achieves competitive performance, e.g., with ResNet50 backbone, it achieves rank1 accuracy of 95.1%, 88.2%, 79.1% and 71.6% on Market-1501, DukeMTMC-ReID, MSMT17 and CUHK03 Detected, respectively, outperforming many state-of-the-art works